The Possibilities of Implementation of the Rights of the Child in Children’s Day Care Centres - Gudžinskienė, Vida; Raudeliūnaitė, Rita; Uscila, Rokas (Pedagogika, 2016)
As economic and cultural changes proliferate in our society, there is an increasing number of families the functioning of which disrupted – they are called social risk families. Social risk families are dominated by such negative factors as alcohol consumption, violence, negligence, failure to comply with societal norms, which are observed by growing up children every day. Gradually children growing up in social risk families become socially injured and need exceptional assistance. In order to assist socially injured children children’s day care centres are established, one of the functions of which is to implement children’s rights. The objective of the study: to theoretically and empirically validate the possibilities of children’s day care centres to implement children’s rights. The subject of the study – the possibilities of children’s rights which are implemented in children’s day care centres. The methods of the study: theoretical methods – the analysis of scientific literature, documents. Empirical methods – a questionnaire survey (instrument – questionnaire), which was aimed at collecting information on the implementation of socially injured children’s rights attending children’s day centres. 255 children, who attend day centres in rural areas, participated in the study. The age limit of children is not less than 14 years and not more than 18 years and parents of whom gave permission that their child could participate in the study. Such children’s age span was chosen, taking into consideration the fact that the children of such age are sufficiently mature and able to adequately express their opinion (the United Nations Convention on the Rights of the Child (1989), G. M. Biegel (2009). The statistical methods of data analysis: descriptive statistics (the analysis of a frequency distribution), Spearman’s correlation coefficient. The results of the study. The documents regulating the activity of children’s day care centres and the educational, socio-cultural activities, which are performed in the centres, and the material assistance, which is provided there, create the preconditions for the implementation of socially injured children’s rights. The empirical study on the implementation of children’s rights in children’s day care centres established that: a favourable psychological atmosphere which is created by the employees in day care centres and the carried out activities create conditions to implement the rights of the majority of socially injured children (a right to be not discriminated, free, healthy, respected, supervised, a right to a cultural activity, leisure and rest, education, (self-) development, a right to express their opinion, be provided for and supervised); the implementation of children’s rights in children’s day care centres is aggravated by a considerable distance between the children’s place of residence and a day care centre. Consequently, part of children stay in a day care centre briefly, they give little or no time for doing homework, participate in sociocultural activities rarely. Part of children have their rights to education and (self-)development, thoughtful and comprehensive leisure partly ensured; more than half of the investigators do not receive material assistance in day care centres. Children’s day care centres only partly ensure a children’s right to be provided for and healthy. It is appropriate to organise the ride of children in children’s day centres, which are in rural areas, in such a way that conditions would be created to all the children, who attend a day care centre, to participate both in educational and sociocultural activities.